POPULATION DYNAMICS OF BOLEOPHTHALMUS BODDARTI IN THE MEKONG DELTA, VIETNAM - Q. M. Dinh (Journal of Animal and Plant Sciences, 2017)
Boleophthalmusboddarti has been increasingly being fished, but littleis knownabout its population dynamics. This study aims to providesome basic parameters of its population biology used for fishery management. A total of 1702 individualscollected by deep gill net along the mudflat in the Mekong Delta, Vietnam, from March 2013 to February 2014.Data analysis showed that the male to female B. boddartiratio was nearly 1:1.The parameters of von Bertalanffy growth function fitting to the length frequency data were L∞= 16.8 cm, K = 0.79 yr-1 and t0 = –0.24 yr-1. The longevity (tmax) and the growth performance (Φ’) were 3.55 yrs and 2.35, respectively. The fishing mortality (F = 0.30 yr-1) and natural mortality (M = 1.83 yr-1) amounted for 14.1% and 85.9% of the total mortality (Z = 2.13 yr-1), respectively. There were two recruitment peaks separated by an interval of 6 months and relative yield-per-recruit and biomass-per-recruit analyses gave Emax = 0.737, E0.1 = 0.618 and E0.5 = 0.348. This study reported that this mudskipper could be potential for future aquaculture due to high growth constant (K), and the local government should require fisherman to change the deep gill net mesh size for the future sustainable exploitation and development.
Keywords: mortality indices; longevity; growth performance; exploitation rate